Jamu: An Ethnomedicine Study and Local Knowledge of Jamu Makers in Health Practices - Zulfa Safitri Kusumaningrum; Vania Pramudita Hanjani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
Traditional herbal medicine as an ethnomedicine has more meaning than a medicinal function, but also an ancestralheritage that is preserved for generations and represents cultural values and identity. Along with the advancement ofscience, modern medicinal products develop significantly, and this becomes a challenge to maintain the existence oftraditional herbal medicine. This article explores the efforts of jamu makers to maintain their cultural heritage andcontribute to health practices. This research was conducted in Wonolopo Village, Mijen Sub-district, Semarang, involving three jamu maker informants, each of whom uses different techniques in the jamu making process. Theethnographic method was used to obtain holistic data through participant observation and in-depth interviews ofinformants' experiences in making jamu. The results showed that jamu makers play an important role in preservinglocal knowledge of jamu making through three methods. First, using the traditional process of pounding. Second,semi-traditional by blending. Finally, using sophisticated and more efficient machine technology. Jamu is believed to provide many benefits to cure diseases and maintain health.